When Christians first met Muslims : a sourcebook of the earliest Syriac writings on Islam - Penn, Michael Philip, (University of California Press, 2015)
"The first Christians to meet Muslims were not Latin-speaking Christians from the western Mediterranean or Greek-speaking Christians from Constantinople but rather Christians from northern Mesopotamia who spoke the Aramaic dialect of Syriac. Living in what constitutes modern-day Iran, Iraq, Syria, and eastern Turkey, these Syriac Christians were under Muslim rule from the seventh century to the present, wrote the earliest and most extensive accounts of Islam, and described a complicated set of religious and cultural exchanges not reducible to the solely antagonistic. Through its critical introductions and new translations of this material, When Christians First Met Muslims allows scholars, students, and the general public to explore the earliest interactions of what eventually became the world's two largest religions" -- Provided by publisher.